Patterns of species richness and abundance among cactus communities receiving different rainfall levels in the semiarid region of Brazil - Paulo Sérgio Monteiro Ferreira; Sérgio de Faria Lopes; Dilma Maria de Brito Melo Trovão (Acta Botânica Brasílica)
ABSTRACT This study examines the variation in cacti species richness and abundance among sites with different average rainfall and soil types. We assessed a total of 3,660 individuals of six species of Cactaceae: Cereus jamacaru, Melocactus zehntneri, Pilosocereus gounellei, Pilosocereus pachycladus, Tacinga inamoena, and Tacinga palmadora. The greatest species richness and abundance of cacti were at locations with low rainfall and more clayey soils. The species studied differed in multidimensional representation, with some species being more positively related to soils with a higher proportion of fine particles (M. zehntneri and P. gounellei), while others were negatively related to soils with a higher proportion of coarser particles (T. inamoena) or positively related to areas with higher rainfall and vegetation cover (C. jamacaru and P. pachycladus). The differential responses of the species of Cactaceae studied in relation to the gradients analyzed demonstrates the need for more research into the relationship between cacti and environmental variables in semiarid ecosystems with high environmental heterogeneity.